Implementation Of The Independent Curriculum In Improving The Numeracy Of Grade IV Students - Kospian, Waode Herdas; Supriadi, Supriadi; Rahmawati, Rahmawati (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
This study aims to determine the implementation of the independent curriculum in improving the numeracy of fourth grade students of SDN Batangase Maros in the 2024 school year. This type of research is descriptive qualitative research. Subjects are teachers and students of class IV-A SDN 24 Batangase Maros. Objects totaled 26 people, 14 male students and 12 female students. Data collection was done by observation, interview and documentation. Activities in data analysis are data reduction, data presentation, and conclusions. The data validity test includes credibility, transferability, dependability and confirmability. Based on the results of this study, it shows that the implementation of the independent curriculum affects students' numeracy skills through the application of number concepts in the material of fraction arithmetic operations in everyday life during the learning process. The low numeracy skills of students are caused by the lack of awareness of the importance of numeracy in helping to solve everyday problems. In practice, numeracy can help students improve reasoning skills and understanding of mathematical concepts, as well as improve speed and accuracy in performing fraction counting operations and solving problems in various life contexts using symbols and numbers related to mathematics. The barriers faced by students in numeracy are: difficulty understanding basic mathematical concepts such as numbers, problem solving in learning, lack of motivation, and the method of teaching.